2015
DOI: 10.1007/s11665-015-1593-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydroxyapatite Nano-particles on the Mechanical and Tribological Properties of Orthopedic Cement-Based Nano-composites Measured by Nano-indentation and Nano-scratch Experiments

Abstract: The aim of this study was to examine the mechanical and tribological properties of a commercially available bone cement by incorporating nano-sized hydroxyapatite using nano-indentation and nano-scratch experiments. In order to achieve this goal, the nano-composite cement samples with different amounts of commercial nano-hydroxyapatite (HAc), as a bone compatible nano-filler, were prepared via vacuum mixing method. The results indicated that nano-indentation and nano-scratch experiments are acceptable methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Polymethyl methacrylate (PMMA) is extensively applied in different industrial areas, such as aircraft, automotive industries, and biomedical materials, for its excellent properties [1][2][3][4][5][6]. For these widely used materials, mechanical strength is the first and foremost characteristic to ensure safety [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Polymethyl methacrylate (PMMA) is extensively applied in different industrial areas, such as aircraft, automotive industries, and biomedical materials, for its excellent properties [1][2][3][4][5][6]. For these widely used materials, mechanical strength is the first and foremost characteristic to ensure safety [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the heterogeneous biomaterials such as polymers reinforced with hydroxyapatite particles, epoxy/silica nanocomposites, Ti and Ti-TiB composites, dental restorative composites, etc. 1929 have been participated in the mechanical characterization program, while the effect of the material non-homogeneity on the nano-indentation experiment results has not been addressed in these studies. Despite the limited researches about the nano-indentation experiment on heterogeneous materials, this method has been considered valid if different parts of the non-homogeneity were in contact with the indenter during the indentation process 3032 .…”
Section: Introductionmentioning
confidence: 99%
“…Koumoulos et al have studied nanomechanical and nanotribological properties of polymer composites compounded with MWCNTs and single‐walled carbon nanotubes (SWCNTs) using the nanoindentation and nanoscratch procedure, in which the results exhibited an obvious dependency on the percentage of MWCNTs. Asgharzadeh Shirazi et al investigated the mechanical and tribological properties of bone cement with an addition of nano hydroxyapatite (nHA) using nanoindentation and nanoscratch techniques. The results of their investigations revealed that the amount of 10 wt% nHA can play a vital role in achieving the desired improvement of mechanical and tribological properties of the bone cement containing nHA NPs .…”
Section: Introductionmentioning
confidence: 99%
“…Asgharzadeh Shirazi et al investigated the mechanical and tribological properties of bone cement with an addition of nano hydroxyapatite (nHA) using nanoindentation and nanoscratch techniques. The results of their investigations revealed that the amount of 10 wt% nHA can play a vital role in achieving the desired improvement of mechanical and tribological properties of the bone cement containing nHA NPs .…”
Section: Introductionmentioning
confidence: 99%